Sleep Disturbances, Melatonin, and Tryptophan Metabolism in Irritable Bowel Syndrome: A Comprehensive Review - Kiersznowska, Nina; Buchman, Małgorzata; Bogacka , Anna; Górowska, Anna; Sobiś, Martyna; Janik, Natalia; Janowiak, Julia; Wadowska, Zuzanna; Lenart, Julia; Miłek, Barbara (Quality in Sport, 2025)
IntroductionIrritable bowel syndrome (IBS) is a chronic functionalgastrointestinal disorder strongly influenced by gut–brain axisdysregulation. Increasing evidence demonstrates that sleepdisturbances significantly worsen gastrointestinal symptoms, visceral hypersensitivity, and overall quality of life in patientswith IBS. Melatonin and tryptophan metabolism appear to play key mechanistic roles linking circadian regulation with gastrointestinal function. Aim To summarize current evidence on the relationship betweensleep disruptions, melatonin physiology, and tryptophanmetabolism in IBS, and to evaluate their potential implicationsfor symptom generation and therapeutic strategies. Material and methods. A literature review was conducted using the PubMed databasewith the keywords: “irritable bowel syndrome (IBS)”, “sleepdisturbance”, “sleep quality”, “melatonin”, “tryptophan”, “gut–brain axis”, “circadian rhythm”, and “visceralhypersensitivity”. Studies including clinical trials, observational research, systematic reviews, meta-analyses, and experimental models were evaluated. Results IBS is consistently associated with reduced sleep efficiency, prolonged REM latency, and increased nocturnal arousals, which correlate with greater abdominal pain severity and altered bowel patterns. Melatonin produced in the gastrointestinal tract influences motility, visceral sensitivity, and mucosal immunity, and clinical trials indicate thatsupplementation may improve both sleep quality and IBS symptoms. Dysregulated tryptophan metabolism, includingserotonin imbalance and stress-driven activation of the kynurenine pathway, further contributes to sleep disruptionand symptom exacerbation. Conclusion Sleep disturbances are a key but often underrecognized driver of IBS symptom severity. Mechanistic links involvingmelatonin and tryptophan pathways highlight the importanceof circadian and neuro-enteric regulation.